7-Aryl-triazolyl-substituted sulfocoumarins are potent, selective inhibitors of the tumor-associated carbonic anhydrase IX and XII. (1st November 2016) - Nocentini, Alessio; Ceruso, Mariangela; Carta, Fabrizio; Supuran, Claudiu T.
Abstract: Sulfocoumarins behave as interesting inhibitors of the metalloenzyme carbonic anhydrase (CA, EC 4.2.1.1). Here, we report a new series of 7-substituted derivatives which were obtained by the click chemistry approach from 7-propargyloxy-sulfocoumarin and aryl azides incorporating halogens, hydroxy, methoxy and carboxyl moieties in their molecules. The new compounds were screened for the inhibition on four physiologically relevant human CA (hCA) isoforms, the cytosolic hCA I and II and the transmembrane tumor-associated hCA IX and XII. The new compounds did not inhibit the cytosolic isoforms but were low nanomolar inhibitors of the tumor-associated ones hCA IX and XII.